Characterization of the diatom flora in the Lower Mountain Fork (Oklahoma, USA), a novel regulated river with a disjunct population of the diatom Didymosphenia geminata (Bacillariophyta). Issue 2 (3rd April 2017) - Bergey, Elizabeth A.; Desianti, Nina; Cooper, Joshua T.
ABSTRACT: Regulated rivers are novel ecosystems with altered temperature and flow regimes that can be used to test distribution patterns of microscopic organisms, such as diatoms. Our objective was to describe the spatial and seasonal patterns of diatoms in a cold-water, oligotrophic river within a region of warm-water, mesotrophic rivers. The Lower Mountain Fork, in south-east Oklahoma (USA), is maintained as a year-around, stocked fishery by the release of cold, hypolimnetic water from Broken Bow Lake and is the southern-most known site of Didymosphenia geminata in North America. Epilithic diatoms were sampled six times at nine sites over a distance of 15.5 km and, within this area, 27 times at the site of the main Didymosphenia bloom. Percentage composition data were analysed for assemblage composition using multivariate analysis, nutrient specificity using a diatom-based metric, and species associations using similarity profiles. Eighty-eight taxa were found, of which 10 were unidentifiable and included local undescribed species and species clusters. Three species [ Gomphonema ( parvulum morph), Achnanthidium rivulare and Achnanthidium minutissimum ] comprised over 60% of the diatom abundance at all sites, and downstream and seasonal patterns were evident for both these and less abundant taxa. Notably, diatom assemblages in the three sites below the dam were similar to that at the lowermost site, below a much smaller dam. The oligotraphentic diatom assemblage reflected the water chemistry of the river. The Didymosphenia bloom had been scoured by a large spate prior to the study and the species was present at two of the nine sites in low numbers but failed to bloom during the study, possibly because of a trend towards increasing phosphorus concentrations in the reservoir ( Didymosphenia blooms under low P concentrations). No other species shared Didymosphenia 's distribution pattern over the study reach, highlighting the novelty of Didymosphenia 's presence in the river.